2007
DOI: 10.1002/hep.21585
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B viral factors in HBeAg-Negative carriers with persistently normal serum alanine aminotransferase levels

Abstract: Chronic hepatitis B patients with high-normal serum ALT (levels of 0.5-1؋ upper limit of normal) are still at risk of liver disease progression. We thus investigated the correlation between serum ALT level and hepatitis B viral factors in HBeAg-negative carriers with persistently normal serum ALT level (PNALT). Baseline clinical and virological features of 414 HBeAg-negative carriers, including 176 (42.5%) with low-normal ALT (levels of less than 0.5؋ upper limit of normal) and 238 (57.5%) with high-normal ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
109
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 117 publications
(106 reference statements)
8
109
1
5
Order By: Relevance
“…Many initial studies had shown that among patients with CHBV infection with normal ALT, about 50-90% of patients had either minimal changes or chronic persistent hepatitis on biopsy [17][18][19][20]. Recently, however, studies have described contrary findings also [21][22][23][24].…”
Section: Fallacies Of Alt Levels For Prediction Of Liver Injury and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Many initial studies had shown that among patients with CHBV infection with normal ALT, about 50-90% of patients had either minimal changes or chronic persistent hepatitis on biopsy [17][18][19][20]. Recently, however, studies have described contrary findings also [21][22][23][24].…”
Section: Fallacies Of Alt Levels For Prediction Of Liver Injury and Tmentioning
confidence: 99%
“…However in a recent study, that investigated the correlation between serum ALT level and hepatitis B viral factors in HBeAg-negative patients with persistently normal serum ALT level (PNALT), it was found that 47.5% of patients with low-normal ALT (levels of less than 0.5x upper limit of normal) and 63.4% with high-normal ALT had serum HBV DNA level[10 4 copies/ ml. Also compared with HBV carriers with low-normal ALT, those with high-normal ALT were older (41 vs. 37 years, P \ 0.001) [21]. Another study from china showed that serum levels of HBV DNA of the patients in the immune-tolerant stage were high and 94% of them had a HBV DNA higher than 10 6 copies/ml [22].…”
Section: Fallacies Of Alt Levels For Prediction Of Liver Injury and Tmentioning
confidence: 99%
“…In the subgroup analysis, however, only 12 of their 76 subjects with detectable HBV-DNA at study entry went from lownormal to high-normal ALT levels after a follow-up period of 12-77 months, but none of them encountered ALT elevation to abnormal level. 1 This finding is also contradictory to earlier observations: abnormal ALT level was observed between the third and twelfth month of follow-up in all 25 HBeAg-negative subjects with normal baseline ALT but higher HBV-DNA level 5 ; the only 4 subjects with serum HBV-DNA Ͼ10 4 copies/mL at presentation in another study all exhibited ALT elevation during follow-up. 6 We recently followed 1241 asymptomatic HBeAg-negative HBsAg carriers with PNALT for 14,484 person-years and found that the cumulative probability of hepatitis relapse was 5% at the 2-year follow-up and 10% at the 5-year follow-up.…”
mentioning
confidence: 65%
“…Of these studies, only Lin's HBeAg-negative subjects had HBV-DNA levels Ͼ10 5 copies/mL despite that the duration of PNALT was at least 2 years before entry to the study. 1 It appears that age, sex, ethnicity, and duration of PNALT are not likely the reason(s) for this discrepancy (Fig. 1).…”
mentioning
confidence: 94%
See 1 more Smart Citation